2013
DOI: 10.1021/jo302211f
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Library Synthesis Using Complex Substrates: Expanding the Framework of Triterpenoids

Abstract: The remodelling of a natural product core framework by means of diversity-oriented synthesis (DOS) is a valuable approach to access diverse/biologically relevant chemical space and to overcome the limitations of combinatorial-type compounds. Here we provide proof of principle and a thorough conformational analysis for a general strategy whereby the inherent complexity of a starting material is used to define the regio- and stereochemical outcomes of reactions in chemical library construction. This is in contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…Tetraketone 1 was prepared according to our previously published method 18 from doubly-protected bryonolic acid in two steps by oxidation of the Δ8,9 double bond with ruthenium tetroxide under Sharpless conditions. Early analysis of the bichromophoric structure of tetraketone 1 revealed that the ‘bowsprit’ hydrogen H-5 is in γ-position to the keto groups at C-8 and C-11.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tetraketone 1 was prepared according to our previously published method 18 from doubly-protected bryonolic acid in two steps by oxidation of the Δ8,9 double bond with ruthenium tetroxide under Sharpless conditions. Early analysis of the bichromophoric structure of tetraketone 1 revealed that the ‘bowsprit’ hydrogen H-5 is in γ-position to the keto groups at C-8 and C-11.…”
Section: Resultsmentioning
confidence: 99%
“…1416 In this regard, the increase in structural complexity of triterpenoid-like molecules through alteration of their carbocyclic core skeleton can be viewed as a promising tool to study the chemical biology and medicinal chemistry of this natural product family. 1718 …”
Section: Introductionmentioning
confidence: 99%
“…[47] Tw ot ypes of chemical approaches were applied to the di-and triketones 45-47, which were generated from acylated bryonolic acid or its derivatives by oxidative cleavage of the double bond between the steroidal Ba nd Cr ings using ruthenium chloride (Scheme 4a). First, the phototransformation potential of bis-(ketones) 46 and 52 was exploited in aN orrish-Yang reaction to form the novel scaffolds 51, 53,and 54.Second, transannular aldol reactions under different reaction conditions were expediently performed on these polycarbonyl substrates to afford molecules with NP-derived scaffolds (48-50, 55;S cheme 4a).…”
Section: Methodsmentioning
confidence: 99%
“…5). The pH values of the culture media were measured after cultivation of A. oryzae (OE::pksCH-2), [11][12][13][14][15] . c, Diversity-oriented semi-synthetic process that combines heterologous biosynthesis and artificial diversification (this work).…”
Section: Resultsmentioning
confidence: 99%
“…To conduct a successful screening of promising drug leads and biological probes, a compound library should be developed that is diverse with regard to the molecular framework. One strategy for expanding the diversity of natural-product-related scaffolds is to make good use of readily available natural products as starting points [11][12][13][14][15] . Although this semi-synthetic approach has great potential to expand the chemical space of natural products, the limited number of natural products that fulfil the availability and reactivity requirements has hindered the emergence of successful examples.…”
mentioning
confidence: 99%